Strategi Pengembangan Klaster UKM Keripik Gadung di Kabupaten Tulungagung - Siti Asmaul Mustaniroh; Oni Zakiyah; Retno Astuti (Universitas Medan Area, 2019)
The research objective was to determine the cluster development strategy based on product performance and quality and analyze the elements in the institutional cluster of gadung chips in Tulungagung Regency. The superior product of gadung chips in Tulungagung Regency is currently being developed in connection with the government's efforts to improve the regional economy through the application of the One Village One Product (OVOP) concept. The center of the gadung chips industry in Kalidawir Subdistrict, which is still active, produces 25 SMEs. The problems faced by SMEs in developing businesses, individuals, lack of communication and cooperation among SMEs with the Government, limited marketing and technology activities and low product quality. The method used is K-means cluster and FAHP. The results showed that the grouping of SMEs gadung chips based on the performance and quality of the products produced 2 clusters. Cluster 1st consists of 11 small-scale members and cluster 2nd consists of 14 micro business scale. Development strategy of cluster 1st by increasing innovation on product features and cluster 2nd through increased access to capital. The institutions consist of several parties involved including core industries, supporting industries, suppliers, supporting institutions and buyers. The success of the development of the gadung chips industry cluster is highly dependent on inter-institutional cooperation relationships.